Clinicopathological Characteristics and Response to Chemotherapy in Treatment-Naive Epstein–Barr Virus Associated Gastric Cancer: A Retrospective Study - Xie, Tong; Peng, Zhi; Liu, Yiqiang; Zhang, Zhening; Zhang, Xiaotian; Li, Jian; Lu, Ming; Gong, Jifang; Qi, Changsong; Ji, Jiafu; Shen, Lin (Frontiers in Oncology, 2021)
Background: Epstein-Barr virus associated gastric cancer (EBVaGC) is a special subtype of gastric cancer. However, the perioperative treatment plan, as well as the response to chemotherapy were still uncertain. Methods: We retrospectively enrolled patients diagnosed with EBVaGC from Mar 2013 to July 2020 in Beijing Cancer Hospital. Clinicopathological characteristics were recorded. Disease free survival (DFS) were then calculated, and variants affecting DFS were tested in a Cox proportional regression model. Results: 160 consecutive patients were finally included in our study. 96.9% of the patients were adenocarcinoma, while 5 patients had squamous cell carcinoma component. Most (70.9%) of them were poorly differentiated. Prevalent PD-L1 (69%) and minor HER-2 (3.8%) expression were noticed, all of the patients were MMR proficient (pMMR) or microsatellite stable (MSS). Among 33 patients who experienced neoadjuvant therapy, the number of tumor regression grade (TRG) 1, TRG 2 and TRG 3 was 5, 16 and 12, respectively. Patients with advanced tumor stage and T stage showed poorer response. 31 patients experienced first-line chemotherapy, ORR was 33.3% and DCR was 61.9%. 147 patients underwent surgery, 27 of them showed disease recurrence, the 3-year DFS rate was 71.0%. Tumor stage, neoadjuvant chemotherapy, vascular invasion and negative PD-L1 expression were associated with poorer DFS. Vascular invasion was the independent risk factor of DFS. Only 7 patients reached OS with median follow-up time of 14 months. Conclusion: EBVaGC exhibits unique clinicopathological characteristics. Neoadjuvant chemotherapy may not be suitable for EBVaGC and EBVaGC exhibited even poorer response to chemotherapy than EBV negative gastric cancer.